2021
DOI: 10.1016/j.jbc.2021.101331
|View full text |Cite
|
Sign up to set email alerts
|

A retinoic acid receptor β2 agonist attenuates transcriptome and metabolome changes underlying nonalcohol-associated fatty liver disease

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 55 publications
1
17
0
Order By: Relevance
“…Another primary source of fatty acids in the liver is from the influx of free fatty acids from blood [ 69 ], including oleate and palmitate [ 96 ]. There have been few studies of the impact of natural retinoids on hepatic influx of free fatty acids; however, we found that a RARβ2-selective agonist inhibits high-fat-diet induced increases in the mRNA and protein levels of the fatty acid transporter CD36, indicating that this agonist attenuates free fatty acid influx to the liver [ 90 ] ( Figure 2 ). To date, we found no studies reporting the effects of retinoids on lipid export from the liver.…”
Section: Non-alcohol-associated Fatty Liver Diseasementioning
confidence: 94%
See 3 more Smart Citations
“…Another primary source of fatty acids in the liver is from the influx of free fatty acids from blood [ 69 ], including oleate and palmitate [ 96 ]. There have been few studies of the impact of natural retinoids on hepatic influx of free fatty acids; however, we found that a RARβ2-selective agonist inhibits high-fat-diet induced increases in the mRNA and protein levels of the fatty acid transporter CD36, indicating that this agonist attenuates free fatty acid influx to the liver [ 90 ] ( Figure 2 ). To date, we found no studies reporting the effects of retinoids on lipid export from the liver.…”
Section: Non-alcohol-associated Fatty Liver Diseasementioning
confidence: 94%
“…We discovered that highly selective synthetic RARβ2 agonists reduce the mRNA and protein levels of multiple gene products (including SREBF, PPARG, and FASN) that are involved in lipogenesis in the liver in a high-fat-diet (HFD)-induced NAFLD mouse model [ 89 , 90 ] ( Figure 2 ). Fructose and sucrose intake promotes de novo lipogenesis in the liver [ 91 , 92 ], and a recent pre-clinical study indicates that a fructokinase (also called ketohexokinase) inhibitor improves NAFLD/NASH [ 91 ].…”
Section: Non-alcohol-associated Fatty Liver Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…Metabolomics analysis can provide the global metabolic profile and identify the differently expressed metabolites. The integrative analysis of transcriptome and metabolome has been increasingly used to investigate the complicated mechanisms of liver diseases ( Zhao et al, 2020 ; Tang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%